Effect of Reaction Time on Biodiesel Production from Palm Fatty Acid Distillate by Using PTSA as a Catalyst. Issue 1 (December 2020) - Burmana, A D; Tambun, R; Haryanto, B; Alexander, V
Abstract: This study aims to determine the effect of reaction time on the production of biodiesel (methyl ester) from palm fatty acid distillate (PFAD) by using para-toluene sulphonic acid (PTSA) as a catalyst. The reaction carried out is the esterification reaction which reacts PFAD with methanol to produce methyl esters and water. In this study, the molar ratio of methanol to PFAD is 6:1 and the reaction is carried out at 65 °C. The amount of PTSA catalyst used is 5%, 10%, 15%, and 20% of the amount of fatty acids. Acid value observation is carried out at the reaction time of 60 minutes, 75 minutes, 90 minutes, 105 minutes, and 120 minutes. The results obtained indicate that the optimum conditions for producing biodiesel from PFAD are with a reaction time of 105 minutes and a catalyst amount of 15%. The acid value obtained does not decrease again or the amount of fatty acids converted to methyl esters does not increase again when the reaction time and the amount of catalyst are increased. The lowest acid value at this optimal condition is 13.37 mg KOH/g, and in this condition, 95.84% of the fatty acid is converted to methyl ester.